Performance of graphene-based hydrogel in oil removal using graphene oxide derived from powder and flake graphite - Ng, L.Y.; Lee, J.J.; Ng, C.Y.; Mahmoudi, E.; Hairom, N.H.H.; Ong, C.B. (2020)
Graphene-based hydrogel had been formed by chemical reduction process of graphene oxide using ascorbic acid as a reducing agent in this study. Oil adsorption capacity of the hydrogels that were synthesized using different parameters, including type of graphene oxide feedstocks (powder or flake graphite), concentration of graphene oxide used (2 mg/mL or 5 mg/mL), as well as the amount of ascorbic acid added into the graphene oxide (5 grams or 8 grams), had been evaluated in this work. Fourier Transform Infrared Spectroscopy (FTIR) results showed that the oxygen-containing functional groups which were initially present in the graphene oxide could be removed or reduced to form the 3-dimensional π-π interactions hydrogel. In overall, hydrogel produced from flake graphene oxide with the use of higher concentration of graphene oxide (5 mg/mL) and the lower amount of ascorbic acid (5 g), showed the best performance in oil adsorption capacity. The hydrogel produced from these parameters showed the highest adsorption capacity of 7.90 g of oil adsorb per g of hydrogel. This study has provided useful information on the functional groups of graphene-based hydrogels in addition to their oil adsorption capability.